Cementless Short Stems in Total Hip Arthroplasty: Chances and Limits - Afghanyar, Yama; Kutzner, Karl Philipp; Pfeil, Joachim; Drees, Philipp; Rehbein, Philipp; Dargel, Jens (The Journal of Hip Surgery, 2024)
In recent decades, a large number of cementless short stems have been introduced to the market. The concept aims at saving soft tissue using minimally invasive surgery and at the same time preserving as much bone as possible. In particular, the latest generation of short stems, which are implanted using a calcar-guided round-the-corner technique, are attracting increasing attention. An individualised resection level allows individual stem alignment and thus an ideal reconstruction of the hip anatomy. The early clinical results of short-stem total hip arthroplasty (THA) are promising and have led to an expansion of the indications and limitations for the use of short stems. In particular, the individual positioning in valgus or varus and the resulting individual metaphyseal or metadiaphyseal anchorage offers various possibilities to reconstruct even abnormal joint morphologies. Consequently, short stems are increasingly used in patients with complex anatomical variations or in cases of osteonecrosis of the femoral head. In some various cases, they can also be used in revision or conversion arthroplasty. In some patients, short stems can also be used after femoral neck fracture. Currently, scientific data on those areas of indication of short-stem THA is scarce.
Keywords: short stem; total hip arthroplasty; cementless